2020
DOI: 10.1111/aogs.13987
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiovascular hemodynamics in type 1 diabetic pregnancies at near‐term gestation

Abstract: Introduction Poor glycemic control in maternal type 1 diabetes mellitus during pregnancy can affect fetal cardiac and placental function. However, studies concerning fetal central hemodynamics have revealed conflicting results. We hypothesized that in pregnancies complicated by maternal type 1 diabetes, fetal cardiovascular and placental hemodynamics are comparable to the control fetuses at near‐term gestation. In addition, we investigated the relation between newborn serum biomarkers of cardiac function and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Gestational diabetes mellitus (GDM) is the most common metabolic disease during pregnancy, with an overall prevalence of 6%−13% ( 10 , 11 ). In patients with gestational diabetes, maternal metabolic abnormalities lead to impaired fetal cardiovascular hemodynamics through a variety of mechanisms, including decreased cardiac output and increased aortic isthmus' flow velocity and pulsation ( 12 ). Furthermore, abnormal blood glucose variability in mothers with diabetes contributes to the development of cardiac diastolic dysfunction, even when obvious cardiac hypertrophy is not observed.…”
Section: Etiology Of Mat At Different Periods Of Growthmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is the most common metabolic disease during pregnancy, with an overall prevalence of 6%−13% ( 10 , 11 ). In patients with gestational diabetes, maternal metabolic abnormalities lead to impaired fetal cardiovascular hemodynamics through a variety of mechanisms, including decreased cardiac output and increased aortic isthmus' flow velocity and pulsation ( 12 ). Furthermore, abnormal blood glucose variability in mothers with diabetes contributes to the development of cardiac diastolic dysfunction, even when obvious cardiac hypertrophy is not observed.…”
Section: Etiology Of Mat At Different Periods Of Growthmentioning
confidence: 99%
“…In addition, clinical studies have found that THBS1 is upregulated in placental trophoblast cells of preeclampsia pregnant women, and subsequent animal experiments have shown that overexpression of THBS1 inhibits the cAMP signaling pathway and affects syncytialization of trophoblast cells, thereby inducing preeclampsia (31,32). Lehtoranta et al found that decreased expression of PDGFRB caused abnormal placental hemodynamics leading to gestational diabetes (33). Based on the GEPIA database, JAG1 and VEGFA exhibited a positive correlation (34), and overexpressing JAG1 promoted the proliferation of endothelial cells (35,36).…”
Section: Discussionmentioning
confidence: 99%